Manajemen Program Nagari Statistik di Kabupaten Dharmasraya - Vovi Ratna Qori; Roni Ekha Putera; Yoserizal Yoserizal (Universitas Serang Raya, 2023)
Nagari Statistik program is implementation form for accurate, integrated, quick and easy to access of statistical data supports. Background of this study was low quality of data in big number of data, so it needs management improvement by government through Satu Data Indonesia program. Therefore, Agency of Communication and Informatics (Diskominfo) and Central Agency of Statistics (BPS), which also support by local government (OPD) in Dharmasraya regency establihed Nagari Statistik program. Kanagarian Sungai Duo as the first of pilot project area of this program. However, there is some obstacles in implementation of this program, both of Agency of Communication and Informatics (Diskominfo) in Dharmasraya regency as an organizer program and the areas (nagari) for this program itself. This study was analyzed to describe the phenomenon at the study sites qualitatively using management function theory to analyze management by Ricky W Griffin that consist of planning, organizing, briefing and supervising of Nagari Statistik program. This study showed that management of this program in Dharmasraya regency has been carried out quite well, although the operational was still not optimal. This phenomenon could be observed from several obstacles, such as limitation of budget and low quality of human resource because there is no statistic expert officer for this program.